Longitudinal evaluation of SMN levels as biomarker for spinal muscular atrophy: results of a phase IIb double-blind study of salbutamol. Issue 5 (28th December 2018) - Tiziano, Francesco Danilo; Lomastro, Rosa; Abiusi, Emanuela; Pasanisi, Maria Barbara; Di Pietro, Lorena; Fiori, Stefania; Baranello, Giovanni; Angelini, Corrado; Sorarù, Gianni; Gaiani, Alessandra; Mongini, Tiziana; Vercelli, Liliana; et al.
Abstract : Background: Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder, due to the loss of function of the survival motor neuron ( SMN1 ) gene. The first treatment for the condition, recently approved, is based on the reduction of exon 7 skipping in mRNAs produced by a highly homologous gene ( SMN2 ). The primary objective of the present study was to evaluate the applicability of the dosage of SMN gene produts in blood, as biomarker for SMA, and the safety of oral salbutamol, a beta2-adrenergic agonist modulating SMN2 levels. Methods: We have performed a 1-year multicentre, double-blind, placebo-controlled study with salbutamol in 45 adult patients with SMA. Patients assumed 4 mg of salbutamol or placebo/three times a day. Molecular tests were SMN2 copy number, SMN transcript and protein levels. We have also explored the clinical effect, by the outcome measures available at the time of study design. Results: Thirty-six patients completed the study. Salbutamol was safe and well tolerated. We observed a significant and progressive increase in SMN2 full-length levels in peripheral blood of the salbutamol-treated patients (p<0.00001). The exploratory analysis of motor function showed an improvement in most patients. Conclusions: Our data demonstrate safety and molecular efficacy of salbutamol. We provide the first longitudinal evaluation of SMN levels (both transcripts and protein) in placebo and in response to a compound modulating the gene expression: SMN transcript dosage in peripheral blood is reliable and may be used as pharmacodynamic marker in clinical trials with systemic compounds modifying SMN2 levels. Trial registration number: EudraCT no. 2007-001088-32.